(MACK - SP) A função f é definida por f(x)= ax + b . Sabe-se que f(-1) = 3 e f(1) = 1. O valor de f(3) é :
a. 0
b. 2
c. -5
d. -3
e. -1

Resolvi assim:
A = y - y = 3 - 1 = 1
x - x -1 - 1

F(1) 1.1 + b = 1
B = 1+ 2 = 3

F(3) = 1. 3 + 3 = 6

Porem a tem a resposta ai :( aonde eu errei?

1

Respostas

2014-04-13T18:45:41-03:00
O ze
f(x)=ax+b
f(-1) = 3 e f(1) = 1

entao
3=-a+b    e    1 = a+b

-a+b = 3
 a+b = 1

-a+b=3             a+b=1
b=3 + a   =>     a+3+a=1
                           2a = -3 +1 = -2/2 = a =-1
 
a= -1

b=3+a
b= 3-1 =2

           f(x) =ax + b
então f(x) = -x + 2

PROVA REAL

f(x)=-x + 2
f(-1)=+1+2 = 3  e f(1) = -1 +2 =1  
                              
3 3 3
Achei meu erro: A = y - y = 3 - 1 = 2 = 1 = -1 <<-- Não é 1
x - x -1 - 1 -2 -1